2010
DOI: 10.1200/jco.2009.25.5158
|View full text |Cite
|
Sign up to set email alerts
|

Single Cycle of Arsenic Trioxide–Based Consolidation Chemotherapy Spares Anthracycline Exposure in the Primary Management of Acute Promyelocytic Leukemia

Abstract: A B S T R A C T PurposeEvent-free survival following all-trans-retinoic acid (ATRA) -based therapy for acute promyelocytic leukemia (APL) averages 70% at 5 years. While arsenic trioxide (ATO) can induce remissions in 95% of relapsed patients, few studies have addressed the integration of ATO into the primary management of APL. This study examines the efficacy of a single cycle of ATO-based consolidation therapy in a treatment regimen designed to decrease exposure to other cytotoxic agents. Patients and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…In a similar ATRA and chemotherapy protocol, postinduction ATO has been used as a substitute for the second cycle of consolidation chemotherapy. 25 The Shanghai 11 and Changsha 26 groups have also demonstrated excellent outcomes with ATRA-and ATO-based induction therapy, although both studies variably used additional cytotoxic agents during induction for high-risk patients. In addition, both studies used substantial postremission chemotherapy (daunorubicin, cytarabine, and homoharringtonine) in multiple cycles of consolidation (Table 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar ATRA and chemotherapy protocol, postinduction ATO has been used as a substitute for the second cycle of consolidation chemotherapy. 25 The Shanghai 11 and Changsha 26 groups have also demonstrated excellent outcomes with ATRA-and ATO-based induction therapy, although both studies variably used additional cytotoxic agents during induction for high-risk patients. In addition, both studies used substantial postremission chemotherapy (daunorubicin, cytarabine, and homoharringtonine) in multiple cycles of consolidation (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although the median followup in this interim analysis is relatively short, it is comparable with several other studies with a median followup that was less than 3 years at the time of reporting. 3,12,13,22,25,26 Nevertheless, we recognize that additional relapses are likely to be seen with a longer period of observation, and a final APML4 analysis will be performed when the last registered patient has been followed for a minimum of 2 years after consolidation. The strategy that most closely resembles APML4 was reported by investigators at the MD Anderson Cancer Center.…”
Section: Discussionmentioning
confidence: 99%
“…In a smaller Phase II trial similar outcomes have been described using a single course of consolidation therapy using cytarabine followed by 30 doses of ATO [20].…”
Section: Consolidation Treatmentmentioning
confidence: 93%
“…Induction therapy using such a regimen yields a complete response (cr) rate in the 90%-95% range 3 . The role of ato became clearer after several studies showed efficacy and safety for ato with or without atra in the relapsed setting 22,23 and, more recently, in first-line induction and consolidation 6,7,[24][25][26] . In 1998, Soignet et al 22 were the first to corroborate reports from China about the efficacy of ato in treating apl by showing that ato is highly efficacious at inducing remission in relapsed disease.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of cr ranged from 84.7% to 97%, and rates of disease-free survival ranged from 72% (median follow-up: 16.5 months) to 97.4% at 5 years 7,24,25,[31][32][33][34][35][36] . The os rates ranged from 86% at 3 years to 91.7% at 5 years 7,24,25,[31][32][33][34][35][36] . One study that combined ato, atra, and idarubicin in induction and ato and atra in consolidation demonstrated equally favourable outcomes in 2-year os rates, regardless of Sanz risk category 7 .…”
mentioning
confidence: 99%